Peran Komunikasi Interpersonal dalam Game Mobile Legends: Bang Bang di Tim Luminous Antapani - Aldy Imam; Prasastiningtyas, Widyapuri (Buana Komunikasi (Jurnal Penelitian dan Studi Ilmu Komunikasi), 2024)
This research was conducted to determine "The Role of Interpersonal Communication in the Game Mobile Legends: Bang Bang (Case Study on the Luminous Antapani Team)". The purpose of this research is to find out the role of communication, the role of certain symbols and why use symbols to communicate with fellow teams. The method in this research is qualitative with a case study type. The data collection techniques used were direct observation at the research location, conducting in-depth interviews with informants and carrying out documentation. In this research, 5 members of the Luminous team, 1 key informant and 4 additional informants. Using Symbolic Interaction Theory, developed by George Herbert Mead (1910), there are several components of communication, namely symbols and meaning, social interaction and the learning process.